Environmental microbiology - Pepper, Ian L. (Elsevier, 2015)
Designed for advanced undergraduate students, graduate students, and environmental professionals, this book builds upon the tremendous success of the previous editions with a comprehensive and up-to-date discussion of environmental microbiology as a discipline that has greatly expanded in scope and interest over the past several decades. From terrestrial and aquatic ecosystems to urban and indoor environments, this edition relates environmental microbiology to a variety of life science, ecology, and environmental science